Regulation of macromolecular synthesis by low molecular weight mediators : proceedings of the Regulation of Macromolecular Synthesis by Low Molecular Weight Mediators Workshop, held at Hamburg-Blankenese, May 29-31, 1979 - Koch, Gebhard; Richter, Dietmar, 1939- (Academic Press, 1979)
Regulation of Macromolecular Synthesis By Low Molecular Weight Mediators.